“The impact of a mental and informational strategy on the achievement of second grade intermediate (Journal of the College of Basic Education, 2024)
The research aims to identify the impact of a mental and informational strategy on the achievement of the second intermediate grade female students in science. The researcher adopted the experimental approach with an experimental design for two equal groups. Sciences according to a mental and informational strategy, and Division (C) to represent the control group that will study the same subject in the usual way. The total number of female students in the two groups reached (64) students; With (31) female students in the experimental group, and (33) female students in the control group; It was statistically rewarded between the members of the two groups in the following variables: (chronological age calculated in months, previous information test, intelligence test, last year grades), and the researcher identified the study material with subjects from the science book for the second intermediate grade, then the researcher formulated behavioral goals, as the number reached (120). ) a behavioral goal. As for the research tool, the researcher built the achievement test, which consisted of (40) objective test items of the multiple-choice quadruple-alternative type, according to the (table of specifications), and the validity, discrimination coefficient, difficulty, effectiveness of alternatives, and stability were verified; Its stability was verified by the split-half method. The researcher used appropriate statistical methods to extract the data, and the results showed that the students of the experimental group outperformed the students of the control group